Sociodemographic, lifestyle and health determinants of suicidal behaviour in Malaysia - Cheah, Yong Kang; Mohd, Azahadi; Phang, Siew Nooi; Abd Manaf, Noor Hazilah (Elsevier, 2018)
Suicide has become a serious matter in both developed and developing countries. The objective of the present study is to examine the factors affecting suicidal behaviour among adults in Malaysia. A nationally representative data which consists of 10,141 respondents is used for analysis. A trivariate probit model is utilised to identify the probability of having suicide ideation, suicide plan and suicide attempt. Results of the regression analysis show that to ensure unbiased estimates, a trivariate probit model should be used instead of three separate probit models. The determining factors of suicidal behaviour are income, age, gender, ethnicity, education, marital status, self-rated health and being diagnosed with diabetes and hypercholesterolemia. The likelihood of adopting suicidal behaviour is lower among higher income earners and older individuals. Being male and married significantly reduce the propensity to engage in suicidal behaviour. Of all the ethnic groups, Indian/others displays the highest likelihood of adopting suicidal behaviour. There is a positive relationship between poor health condition and suicide. Policies targeted at individuals who are likely to adopt suicidal behaviour may be effective in lowering the prevalence of suicide.